2019
DOI: 10.1080/13814788.2019.1639668
|View full text |Cite
|
Sign up to set email alerts
|

Why do Danish junior doctors choose general practice as their future specialty? Results of a mixed-methods survey

Abstract: Background: A well-staffed and an efficient primary healthcare sector is beneficial for a healthcare system but some countries experience problems in recruitment to general practice. Objectives: This study explored factors influencing Danish junior doctors’ choice of general practice as their specialty. Methods: This study is based on an online questionnaire collecting quantitative and qualitative data. Two focus-group interviews were conducted to info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 21 publications
0
19
0
2
Order By: Relevance
“…Several studies have shown that early and frequent contact with general practice during one's undergraduate curriculum has the potential to increase a student's interest in primary care. [1][2][3] Concurrently, higher education is increasingly utilizing novel teaching techniques to enhance learning by increasing the involvement of students in the teaching and learning process. One approach is the use of peer-assisted learning.…”
Section: To the Editormentioning
confidence: 99%
“…Several studies have shown that early and frequent contact with general practice during one's undergraduate curriculum has the potential to increase a student's interest in primary care. [1][2][3] Concurrently, higher education is increasingly utilizing novel teaching techniques to enhance learning by increasing the involvement of students in the teaching and learning process. One approach is the use of peer-assisted learning.…”
Section: To the Editormentioning
confidence: 99%
“…Previous studies have identified that medical practitioners choose to work in core general practice as they perceive it to lack unsociable hours while providing work–life balance and continuity of care. 11 , 12 This may be a limiting factor for GPs choosing to work in GPED services.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, es poco probable que aquellos médicos que postulen al residentado y no hayan participado tengan características muy diferentes a los encuestados; 3) Existen otros factores que podrían ser importantes (tiempo de rotación durante el pre-grado, riesgo de demandas por mala praxis, percepción de habilidades propias, oportunidad de uso de nuevas tecnologías, entre otras) que no fueron evaluados en nuestro estudio [25,32,38] . Estudios con diseños cualitativos podrían ser útiles para identificar otros posibles factores de importancia [39] . Sin embargo, el presente es uno de los primeros estudios que evalúa los factores que son importantes o no para poder elegir una especialidad médica.…”
Section: Elección Y Preferencias De La Especialidad Médicaunclassified